Advising Obese Adults about Diet and Physical Activity in Sousse, Tunisia. (21st February 2013) - Maatoug, Jihene; Harrabi, Imed; Hmad, Sonia; Belkacem, Mylene; Nouira, Asma; Ghannem, Hassen
Abstract : Background . To our knowledge no study has been conducted in Tunisia to describe practice of health care providers towards chronic disease risk factors, particularly among obese adults. Aim . This study is aimed at assessing the level of giving advice on diet and physical activity by health care providers for obese adults comparing to nonobese adults in Tunisia. Methods . A cross-sectional survey was carried out in 2010 for adults aged from18 to 65 years living in the region of Sousse. The questionnaires were administered by an interview made by trained data collectors to standardize the administration of the questionnaire. Anthropometric measurements of height and weight were obtained using a standardized protocol from each participant. Results . The findings from this study indicate that obesity is frequent among adults essentially among women and aged categories. It also shows that obese adults are not adequately diagnosed with few proportion of anthropometric measure evaluation among all the participants. Even if obese participants were significantly more advised than nonobese participants with, respectively, 28.5% to lose weight and 23.8% to increase physical activity, this proportion remains low.